2019
DOI: 10.1213/ane.0000000000004404
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Methadone Reduces Pain and Opioid Consumption in Acute Postoperative Pain: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: Methadone is a potent opioid exerting an analgesic effect through N-methyl-d-aspartate receptor antagonism and the inhibition of serotonin and noradrenaline reuptake. It has also been used in several procedures to reduce postoperative pain and opioid use. This meta-analysis aimed to determine whether the intraoperative use of methadone lowers postoperative pain scores and opioid consumption in comparison to other opioids. METHODS: Double-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 38 publications
5
44
0
Order By: Relevance
“…In our study, the methadone group had a lower incidence of both events in PACU and a lower incidence of nausea during the whole stay on the surgical ward. These findings are comparable with results observed after open bariatric surgery [14], but contradict those of a recent metaanalysis that did not detect this benefit [27]. It is likely this finding was not observed by Machado et al [27] because they included operations with a low incidence of PONV in their meta-analysis, which would require a larger sample size to detect the effect of methadone in reducing these events compared with control groups.…”
Section: Discussionsupporting
confidence: 55%
“…In our study, the methadone group had a lower incidence of both events in PACU and a lower incidence of nausea during the whole stay on the surgical ward. These findings are comparable with results observed after open bariatric surgery [14], but contradict those of a recent metaanalysis that did not detect this benefit [27]. It is likely this finding was not observed by Machado et al [27] because they included operations with a low incidence of PONV in their meta-analysis, which would require a larger sample size to detect the effect of methadone in reducing these events compared with control groups.…”
Section: Discussionsupporting
confidence: 55%
“…First, in order to minimize clinical heterogeneity, we compared methadone to morphine only. It is possible that the use of intraoperative methadone can have greater postoperative analgesic effects when compared to other commonly used intraoperative opioids (e.g., fentanyl) [37,38]. Secondly, we limited our comparison to the intraoperative phase.…”
Section: Discussionmentioning
confidence: 99%
“…9 The beneficial analgesic effects of methadone have been noted in adult and pediatric cardiac surgery. [10][11][12] Murphy et al have demonstrated, in a prospective randomized trial (n = 156: adult cardiac surgery with cardiopulmonary bypass), that intraoperative methadone significantly reduced postoperative pain and rescue opioid requirements, with enhanced patient-perceived quality of pain management. 10 A recent meta-analysis confirmed the superior analgesic and opioid-sparing properties of methadone for acute postoperative pain due to its potent analgesic effects, including N-methyl-Daspartate receptor antagonism, as well as inhibition of serotonin and noradrenaline uptake.…”
mentioning
confidence: 99%
“…10 A recent meta-analysis confirmed the superior analgesic and opioid-sparing properties of methadone for acute postoperative pain due to its potent analgesic effects, including N-methyl-Daspartate receptor antagonism, as well as inhibition of serotonin and noradrenaline uptake. 12 The cumulative literature, together with the findings from Burtoft et al, suggested that methadone could be considered more often for enhanced recovery after cardiac surgery, including minimally invasive cardiac surgery. [8][9][10][11][12] Beyond methadone, what are further options to reduce the high incidence of severe postoperative pain and improve the quality of recovery in this setting?…”
mentioning
confidence: 99%
See 1 more Smart Citation